Mixed Feelings and Vexed Passions: Exploring Emotions in Biblical Literature - Spencer, Franklin Scott (Resources for biblical study, 2017)
A ground-breaking collection exploring the rich array of emotions in biblical literature An international team of Hebrew Bible and New Testament scholars offers incisive case studies of passions displayed by divine and human figures in the biblical texts ranging from joy, happiness, and trust to grief, hate, and disgust. Essays address how biblical characters' feelings affect their relationship with God, one another, and the world and how these feelings mix together, for good or ill, for flourishing or vexation. Deeply engaged with both ancient and modern contexts, including the burgeoning interdisciplinary study of emotion in the humanities and sciences, these essays break down the artificial divide between reason and passion, cognition and emotion, thought and feeling in biblical study. Features Case studies drawn from multiple genres across the Bible: narrative, prophets, poetry, wisdom, Gospels, and letters Helpful select bibliographies of interdisciplinary resources at the end of each essay Critical balance between theory and practice and between method and close textual analysis Distinctive ancient Hebrew and Greek uses of emotional terms and concepts compared with each other and with evolving understandings in Western culture